2018
DOI: 10.1556/030.65.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Helicobacter pylori glmM and 16S rRNA genes correlate with serum TNF-α and IL-1β cytokine fluctuations

Abstract: The proinflammatory cytokines of TNF-α and IL-1β have been reported to be increased in gastric mucosal surfaces in people with Helicobacter pylori infection. Accordingly, this study was conducted to investigate the relationship between the presence of H. pylori genes and the serum oscillations of these cytokines. In this study, DNA was first extracted from the stool samples of infected individuals and used as DNA template to investigate the presence of glmM and 16S rRNA genes in PCR. The ELISA assay was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It has been long known that TNF-α is significantly higher in patients with H. pylori infection than in healthy controls, as well as in those with histologically demonstrated gastritis and peptic ulcers, suggesting that it might contribute to the gastric injuries caused by this infection [98]. Recent findings also verified this statement [96]. The expression of TNF-α is correlated with the bacterial load according to Mansilla-Vivar et al, who pointed out that this cytokine is significantly higher in H.-pylori-positive patients without nodular gastritis, which is a well-known sign of increased bacterial load, than in those with nodular gastritis caused by H. pylori infection [48].…”
Section: Tnf-αmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been long known that TNF-α is significantly higher in patients with H. pylori infection than in healthy controls, as well as in those with histologically demonstrated gastritis and peptic ulcers, suggesting that it might contribute to the gastric injuries caused by this infection [98]. Recent findings also verified this statement [96]. The expression of TNF-α is correlated with the bacterial load according to Mansilla-Vivar et al, who pointed out that this cytokine is significantly higher in H.-pylori-positive patients without nodular gastritis, which is a well-known sign of increased bacterial load, than in those with nodular gastritis caused by H. pylori infection [48].…”
Section: Tnf-αmentioning
confidence: 78%
“…TNF-α is mainly involved in mediating the acute inflammatory responses to Gram-negative bacteria, along with other infectious agents, where it is responsible for a wide spectrum of complications. Therefore, this cytokine mediates the inflammatory responses during infection with H. pylori as a result of the stimulating effect of H. pylori lipopolysaccharide on macrophages, leading to the synthesis of a great amount of TNF-α [ 96 ]. Furthermore, TNF-α acts as both a recruitment and an activator factor for monocytes, macrophages and neutrophils by stimulating their migration to the infection site [ 97 ].…”
Section: The Trialogue Between H Pylori Cytokines...mentioning
confidence: 99%
“…In this pathway,Asymmetric dimethylarginine (ADMA) was the most noticeable metabolism which attracted us. ADMA is an endogenous nitric oxide synthase inhibitor and is associated with endothelial dysfunction, it plays a key role in CVD pathogenesis and atherosclerosis progression ( 25 ). Furthermore, ADMA upregulation is an important and independent risk factor for various CVDs ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that GLMM and 16S rRNA in the feces of HP infected subjects were positively related to plasma levels of TNF-α and IL-1. 28 Finally, HP infection can aggravate the metabolic disorder of subjects with DM and increase the risk factors of arteriosclerosis. 29…”
Section: Discussionmentioning
confidence: 99%